The Effectiveness of Graphic Organizer Strategy to Improve Reading Comprehension in Eleventh Grade Students at SMA Pancasila Ambulu - Rahayu, Titik; Hatip, Mochammad; Oktarini, Widya (ENJEL: English Journal of Education and Literature, 2024)
Reading comprehension is an important point that needs to be considered in reading activities, namely the ability of students to understand the meaning of the contents of a reading text a whole. Graphic organizer strategy, namely as a graphic diagram or chart that represents the relationship directed by the verb thinking skills associated with the importance of students' reading comprehension. This strategy is effective to help students achieve their reading competence because using graphic organizers that focus on critical and creative thinking elements can help students better grasp the meaning of a text. This study followed a simple research design called pre-experimental research, specifically a static group comparison design. The participants were students from SMA Pancasila Ambulu, with 24 students from 11th Science A and 27 students from 11th Science B. The results revealed that the post-test scores of both the experimental and control groups were significantly different, with a level of significance of ≤0.05. This led to rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha). The experimental group scored 90.41 on the post-test, while the control group scored 37.37. This shows a significant difference in reading comprehension levels between students who learned using interactive graphic organizers and those who were taught with student worksheets.